Life satisfaction and work-life balance: the complexities of gender patterning - Brooks, R; Fu, J; Maire, M (SAGE Publications, 2024)
Conventionally, issues connected to work–life balance have been thought to concern women more than men – not least through the promotion of a strongly gendered discourse about the imperative to become a ‘balanced woman’. In this article, however, we draw on interview data from both men and women (in Australia, occupying broadly middle-class social positions) to show the complexities of gender patterning. Specifically, we demonstrate that the cultural imaginary of a ‘balanced life’ as route to life satisfaction was shared equally by the men and women in our sample. Moreover, men were as likely as women to point to the arrival of children as a key ‘fateful moment’ for re-evaluating their own work–life balance. However, gender disparities were evident in both the nature of change that was effected to achieve ‘balance’ and the associated expectations of partners. The article contributes to the gendered theorisation of work–life balance as a cultural norm in contemporary society.